2019
DOI: 10.1080/19768354.2019.1700159
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition in 3T3-L1 adipocytes breaks the crosstalk with tumor cells by suppression of adipokine production

Abstract: Several studies have revealed the functional importance of autophagy in both adipogenesis and carcinogenesis. Here, we investigated autophagy as a link between tumorigenesis and adipogenesis using 3T3-L1 cells, which have been shown to closely mimic the in vivo differentiation process. The relative levels of LC3-II/I showed that autophagy was the highest after 4-6 days of initiation of differentiation and it diminished thereafter. Furthermore, chloroquine (CQ), a late autophagy inhibitor, effectively inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Cells were incubated for 21 days, and the media changed every 3 days. Murine 3T3-L1 preadipocyte cells were cultured and differentiated as previously described ( Hwang and Lee, 2020 ). To assess the effect of autophagy on adipocyte differentiation, the autophagic inhibitor (3-MA), an inhibitor of phosphoinositide 3 kinase that specifically inhibits autophagosome formation at 5 mM (MCE, China), were added to the media before adipogenic differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were incubated for 21 days, and the media changed every 3 days. Murine 3T3-L1 preadipocyte cells were cultured and differentiated as previously described ( Hwang and Lee, 2020 ). To assess the effect of autophagy on adipocyte differentiation, the autophagic inhibitor (3-MA), an inhibitor of phosphoinositide 3 kinase that specifically inhibits autophagosome formation at 5 mM (MCE, China), were added to the media before adipogenic differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…Adipogenesis has been shown to affect the composition and regeneration of adipose tissue during obesity 27 . Since adipocyte differentiation occurs in two steps 28,29 , MitoTam and tamoxifen were added to pre-adipocytes at two different time points (Fig. 7a), and evaluations were performed after completion of adipogenesis (day 9).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that autophagy plays a key role in the process of differentiation and examining the responses of differentiation; thus, autophagy could be a possible marker (Dong and Czaja, 2011;Goldman et al, 2011). In a recent study, its similar impairment of adipocyte differentiation was observed in 3T3-L1 pre-adipocytes in which microtubule -associated protein 1A/1B-light chain-3 (LC-3) was removed (Hwang and Lee, 2020), or the autophagy process was blocked by chemical inhibitors (Park et al, 2017). Another study has also reported that removal of gene 5 or 7 related to autophagy in the mice reduces lipid biosynthesis and decreases overall body mass of fat tissues (Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 80%